White hats to the rescue. (Economist, 2014)
The article discusses the use of professional computer hackers, known as white hats, by technology companies to test for vulnerabilities in their data security infrastructure, a practice known as penetration testing (pentesting). Topics include consumer data breaches and costs to businesses and consumers and comparing security software systems and pentesting strategies.